DESCRIPTION OF CURRENT BLOOD SUGAR LEVELS IN SCHIZOPHRENIC PATIENTS UNDERGOING ANTIPSYCHOTIC THERAPY AT RSKJ SOEPRAPTO BENGKULU - Honesty Salma Junisa; Zamharira Muslim; Nadia Pudiarifanti (Proceeding B-ICON, 2023)
One of the treatments for schizophrenia patients with pharmacology is antipsychotic treatment. Long-term use of antipsychotic drugs can cause side effects in very serious metabolic disorders, such as the risk of obesity, diabetes, and dyslipidemia. The purpose of this study was to determine the description of blood glucose levels during schizophrenia patients undergoing antipsychotic therapy at RSKJ Soeprapto Bengkulu. This research method is descriptive with retrospective data collection on medical records of schizophrenia patients at RSKJ Soeprapto Bengkulu for the period 2022. The number of samples used was 86 schizophrenia patients undergoing antipsychotic therapy. The results of this study showed that most patients were male 68 patients, the age range was 36-45 years old with 26 patients, the longest use of antipsychotic therapy was 2 years with 28 people (33%), the body mass index in schizophrenia patients was normal body mass index with 56 people. The most common single antipsychotic use was Risperidone for as many as 36 patients, for the use of the most combination antipsychotics, Chlorpromazine-Risperidone was 8 patients, and all patients had normal blood glucose levels (100%). This study concludes that blood glucose levels during schizophrenia patients who use single and combined antipsychotic therapy show no increase in blood glucose levels.